IDENTIFIKASI POTENSI BAHAYA DAN PENGENDALIANNYA PADA PEKERJAAN BEKISTING ALUMA SYSTEM PROYEK X - Kusumo Dradjad Sutjahjo; Tri Wulan Sari; Fadhlina Sahara (Construction and Material Journal, 2021)
Work at height is a job with a high risk of accidents, such as in the formwork aluma system. Weak supervision and a lack of knowledge of the workforce on potential hazards and risk control of the formwork aluma system are some of the causes of the high incidence of work accidents in this work. This research was conducted on the formwork aluma system of the BRI Gatot Subroto tower project, South Jakarta. The goal is to determine the potential hazards and risk control of aluma system formwork. Risk analysis is carried out using the AS / NZS 4360: 2004 standard to determine the level of risk to the potential hazards of the aluma system formwork. Potential hazards in the formwork aluma system are falling, bumping, being cut, punctured and crushed, with the level of risk being at high, substantial, medium and low levels. Risk control is carried out by the control hierarchy, namely elimination, substitution, engineering, administration, and control of PPE. Keywords: AS / NZS 4360: 2004, Risk Analysis, Hazards, Aluma System Formwork.